Fractal Sturm–Liouville Theory - Alireza Khalili Golmankhaneh; Zoran Vidović; Hüseyin Tuna; Bilender P. Allahverdiev (Fractal and Fractional)
This paper provides a short summary of fractal calculus and its application to generalized Sturm–Liouville theory. It presents both the fractal homogeneous and non-homogeneous Sturm–Liouville problems and explores the theory’s applications in optics. We include examples and graphs to illustrate the effect of fractal support on the solutions and propose new models for fractal structures.